Basic Enzymology of Blood Coagulation* - Seegers, W. H (Thrombosis and Haemostasis, 1965)
I have considered the accuracy of the “enzyme cascade” sequence or “waterfall sequence” for blood clotting proposed recently. My remarks are not intended to be exhaustive, but rather representative of a perspective. I regard these presentations as being at the speculative level of science, created with a wild use of the imagination. Some of the clotting factor precursors that are supposed to be converted in succession to active enzymes may not exist and certainly are not known to be enzymes. I find it against my sense of order to believe that six proteolytical enzymes are needed to get thrombin. That would require six special sites in proteins where each enzyme does its work. Each enzyme would not split the other five sites if located as single or multiple frequencies in the five other substrates. While creating hypothetical enzymes and assigning Roman numerals to them the well documented function of the best known enzyme; namely, thrombin is disregarded. The capacity of prothrombin to form derivatives is disregarded. This immediately places the superstructure on a false base. The sequence is definitely not in accurate order. There is no elaborate mobilization of chemical events on the periphery of prothrombin which leads to doing something to prothrombin. The second known enzyme, autoprothrombin C, is included in the plasma-platelet system (intrinsic) whereas its main, if not exclusive place, is in the conversion of prothrombin to thrombin when tissue-plasma-platelet mechanisms are in operation. What is meant by t he term prothrombin is not clarified, and the way in which the required phospholipid originates is not accounted for. If there is a factor XII it is not the exclusive way to create conditions that will initiate prothrombin activation in the plasma-platelet system. Most of the steps postulated could only be accurate if it were possible to deny important conclusions stated in papers which are not at all considered. Evidently refutation of facts in these papers was not possible and a parochial kind of authority was promoted1 ) on the basis of “consistent with most of the current investigations”. I like to recal11 ) the words of Henry David Thoreau: “Any man more right than his neighbor, constitutes a majority of one.” The advances in prothrombin chemistry are sufficiently substantial for the formulation of a conceptual theme consistent with principles of enzymology, and as I have indicated above, can also serve as a clarification of the proposed cascade or waterfall diagrams.